Post-operative pain after ultrasound transversus abdominis plane block versus trocar site infiltration in laparoscopic nephrectomy: a prospective study - Araújo,Ana M. (2017)
Abstract Background Transversus abdominis plane (TAP) block is useful in reducing post-operative pain in laparoscopic nephrectomy compared to placebo. The purpose of this work is to compare post-operative pain and recovery after TAP block or trocar site infiltration (TSI) in this surgery. Methods A prospective, single blinded study on patients scheduled for laparoscopic nephrectomy. Patients were assigned to two groups: TSI Group: trocar site infiltration at the end of surgery; TAP Group: unilateral ultrasound-guided TAP block after induction. Sevoflurane and remifentanil, in a target controlled infusion mode, were used for maintenance of general anesthesia. Before the end of surgery paracetamol, tramadol and morphine were administered. Visual analogue scale (VAS 0-100 mm) at rest and with cough was applied in three moments: in recovery room (T1 at admission and T2 before discharge) and 24 h after surgery (T3). Pain scores with incentive spirometer were also evaluated at T3. In recovery, morphine was administered as a rescue drug whenever VAS > 30 mm. Time to oral intake, chair sitting, ambulation and length of hospital stay were evaluated 24 h after surgery. Statistical analysis: Student's t-test and Chi-square test, and linear regression models. A p-value < 0.05 was considered significant. Data are presented as mean (SD). Results Forty patients were enrolled in the study. The primary outcome variable, VAS pain scores did not show a statistical significant difference between groups (p > 0.05). VAS at rest (TAP vs. TSI groups) was: T1 = 33 ± 29 vs. 39 ± 32, T2 = 10 ± 9 vs. 17 ± 18 and T3 = 7 ± 12 vs. 10 ± 18. VAS with cough (TAP vs. TSI groups) was: T1 = 51 ± 34 vs. 45 ± 32, T2 = 24 ± 24 vs. 33 ± 23 and T3 = 20 ± 23 vs. 23 ± 23. VAS with incentive spirometer (TAP vs. TSI groups) was: T3 = 21 ± 27 vs. 21 ± 25. Intraoperative remifentanil consumption was similar between TAP (0.16 ± 0.07 mcg.kg-1.min-1) and TSI (0.18 ± 0.9 mcg.kg-1.min-1) groups. There were no differences in opioid consumption between TAP (4.4 ± 3.49 mg) and TSI (6.87 ± 4.83 mg) groups during recovery. Functional recovery parameters were not statistically different between groups. Conclusions Multimodal analgesia with TAP block did not show a significant clinical benefit compared with trocar site infiltration in laparoscopic nephrectomies.